1996
DOI: 10.1111/j.1469-7610.1996.tb01459.x
|View full text |Cite
|
Sign up to set email alerts
|

Working Memory in Children with Autism and with Moderate Learning Difficulties

Abstract: We asked whether children with autism are specifically impaired on tests of working memory. Experiment 1 showed that children with autism were at least as likely as normal children to employ articulatory rehearsal (criterion: evincing the "word length effect") and that they had superior spans to that of children with moderate learning difficulties. In Experiment 2, participants were given "capacity tasks" in order to examine group differences in the capacity of the central executive of working memory. The perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
166
7
7

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 199 publications
(193 citation statements)
references
References 46 publications
13
166
7
7
Order By: Relevance
“…A consistent finding is their impaired immediate verbal serial recall (Henry & MacLean, 2002;Henry & Winfield, 2010;Hulme & Mackenzie, 1992;Russell, Jarrold, & Henry, 1996;Schuchardt, Gebhardt, & Mähler, 2010;Van der Molen, Van Luit, Jongmans, & Van der Molen, 2007). This is found with chronological age-matched peers, but, more significantly, with mental age (MA) matched peers (e.g., Henry & MacLean, 2002;Henry & Winfield, 2010;Hulme & Mackenzie, 1992;Russell et al, 1996).…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations
“…A consistent finding is their impaired immediate verbal serial recall (Henry & MacLean, 2002;Henry & Winfield, 2010;Hulme & Mackenzie, 1992;Russell, Jarrold, & Henry, 1996;Schuchardt, Gebhardt, & Mähler, 2010;Van der Molen, Van Luit, Jongmans, & Van der Molen, 2007). This is found with chronological age-matched peers, but, more significantly, with mental age (MA) matched peers (e.g., Henry & MacLean, 2002;Henry & Winfield, 2010;Hulme & Mackenzie, 1992;Russell et al, 1996).…”
Section: Introductionmentioning
confidence: 61%
“…The current findings, therefore, provide new evidence regarding strategic behaviour and word length effects in adolescents with mild ID, supporting a 'developmental' perspective (Zigler & Balla, 1982) that at least some aspects of verbal strategy development proceed in line with mental age. Importantly, the current findings were not subject to the potentially confounding effects of verbal output at recall or auditory presentation (e.g., Poloczek et al, 2014;Russell et al, 1996).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Brown, 1974;Connors et al, 1998;Henry & MacLean, 2002;Henry & Winfield, 2010;Mähler et al, 2009). Yet some inconsistency in the literature is also apparent: a few authors have reported that children with ID perform more poorly than MA comparisons (Russell et al, 1996;van der Molen et al, 2009). With respect to verbal fluency, Conners et al (1998) found no differences in performance between children with ID and MA comparisons on a letter fluency task; similarly, Henry (2010) found no group differences using a category fluency task.…”
Section: Introductionmentioning
confidence: 99%